PHILOSOPHY OF SCIENCE PERSPECTIVE ON QUALITY OF FINANCIAL STATEMENTS - Lativa Lativa (Asosiasi Dosen Muda Indonesia, 2024)
Financial statements reflect the good and bad performance of the company. High quality financial reports indicate that the information contained therein can be used in decision making. The influence of financial statements is very large for companies, so sometimes some companies violate or manipulate the company's financial statements. The ontological perspective of accounting is actually not only technical, but there are standards that apply, including Generally Accepted Accounting Principles or commonly abbreviated as GAAP which contains the rules of financial statements reported to interested parties. The epistemology aspect is truth seen from the point of view of why and how true facts occur and can be verified or proven. The embodiment of empiricism in accounting (Beam, 1969) emphasizes factual information, accurate measurements and data objectivity. According to SFAC No. 2 (FASB, 1978), the resulting accounting information must meet the qualifications of relevant and reliable in order to be useful to users of financial statements. Accounting and its developers must always be accompanied by certain relevant values so that the practice of accounting does not run itself off the track. Accounting is essentially a moral and discursive practice, therefore the development and practice of accounting ideally needs to be done with responsibility. Kuhn's thinking which has criteria where one (scientific) theory is considered better than other theories is reinforced by Rofiq's statement which describes these criteria including Accuracy, Consistency, Scope, Simplicity and Fruitfulnees must be reflected in the quality of financial statements presented by financial preparers.